Developing Imaginative Creativity Through Open-Ended Questions in History Learning: A Qualitative Literature Review - Sona Minasyan; Nana Supriatna (Yayasan Perguruan Kampus, 2024)
This qualitative literature review examines the role of creative pedagogy in improving history education, focusing on the Indonesian context. Drawing on the work of N. Supriatna and N. Maulida (2020) and other key educational theorists, this study explores how creative imagination, especially through open-ended questions, can transform traditional methods of rote learning into dynamic exercises in critical thinking. Integrating creative strategies such as role-playing, storytelling, and interdisciplinary projects has been shown to increase student engagement, deepen understanding, and develop important critical thinking skills. These methods allow students to explore historical events from multiple perspectives, encouraging empathy and a nuanced understanding of historical complexities. The review identifies problems inherent in traditional approaches to history teaching, which often prioritize memorization of facts over analytical skills, and highlights the need for educational reforms that emphasize creative thinking. Effective implementation of these pedagogies requires comprehensive teacher training and supportive educational policies that value creativity alongside factual knowledge. The findings suggest a need for change in history education that prepares students to address contemporary issues with creativity and informed critical analysis, thereby promoting their development as active and reflective citizens. This review highlights the transformative potential of integrating creative approaches into history curricula, suggesting that such innovations are critical to enriching the learning experience and enhancing students' cognitive abilities in both understanding history and solving real-world problems.